The effect of acute exercise on objectively measured sleep and cognition in older adults - Sewell, Kelsey R.; Smith, Nathan D. W.; Rainey-Smith, Stephanie R.; Peiffer, Jeremiah; Sohrabi, Hamid R.; Erickson, Kirk I.; Brown, Belinda M. (Frontiers in Psychology, 2023)
Background: Exercise can improve cognition in ageing, however it is unclear how exercise influences cognition, and sleep may partially explain this association. The current study aimed to investigate whether objectively measured sleep mediates the effect of an acute exercise intervention on cognition in older adults. Methods: Participants were 30 cognitively unimpaired, physically active older adults (69.2 ± 4.3 years) with poor sleep (determined via self-report). After a triple baseline cognitive assessment to account for any natural fluctuation in cognitive performance, participants completed either a single bout of 20-minutes of high intensity exercise on a cycle ergometer, or a control condition, in a cross-over trial design. Cognition was measured immediately post-intervention and the following day, and sleep (total sleep time, sleep onset latency, sleep efficiency, % of rapid eye movement sleep, light sleep and deep sleep) was characterised using WatchPAT TM at baseline (5 nights) and measured for one night after both exercise and control conditions. Results: Results showed no effect of the exercise intervention on cognition immediately post-intervention, nor an effect of acute exercise on any sleep variable. There was no mediating effect of sleep on associations between exercise and cognition. However, a change from baseline to post-intervention in light sleep and deep sleep did predict change in episodic memory at the ~24 hour post-intervention cognitive assessment, regardless of intervention condition. Discussion: There was no effect of acute high intensity exercise on sleep or cognition in the current study. However, results suggest that associations between sleep and cognition may exist independently of exercise in our sample. Further research is required, and such studies may aid in informing the most effective lifestyle interventions for cognitive health.